A Multicenter Point-Prevalence Survey of Antibiotic Use in Haiti, June–August 2019: Findings and Implications. (October 2020) - Sati, Hatim; Lucien, Mentor Ali Ber; Hsieh, Jenny; Theodule, Jean-Baptiste; Cerpa, Mauricio; Bruinsma, Nienke; Joseph, Gerard; Dely, Patrick; Boncy, Jacques; Ramon-Pardo, Maria del Pilar
Abstract : Background: Inappropriate use of antibiotics in hospitalized settings contributes to the selection and emergence of antimicrobial-resistant pathogens. This trend is particularly challenging in resource-constrained settings where the high burden of infectious diseases, combined with suboptimal infection prevention and control measures, are further complicated by limited access to reliable microbiological services to inform antimicrobial prescription at the patient level. In this study, we describe the use of antibiotics in selected Haitian hospitals; we aimed to create a baseline to inform antimicrobial stewardship interventions. Methods: WHO/PAHO Hospital Antibiotic Use Point Prevalence Survey (HAMU-PPS) were conducted in 6 acute-care Haitian hospitals: La-Paix and Hospital-Albert (June 2019) and Hospital-Universitaire-Justinien, Hospital-Bienfaisance-de-Pignon, Hospital-Sacre-Coeur-de-Milot, and Hospital Immaculee-Conception-des-Cayes (July-August 2019) in 6 different cities. Trained data collectors completed electronic forms using REDCap software including data related to antibiotic use, indications, and utilization of laboratory services from medical records of all inpatients meeting study inclusion criteria. Analyses were done using Microsoft Excel software (v2016). Results: In total, 510 inpatients records were surveyed. Patients ages ranged from 0 to 92, with median age of 27 years (IQR, 4–47); 269 were women (57.7%) and 239 were men (46.9%). The prevalence of antibiotic use was 73% (95% CI, 68.2%–81.8 %); this prevalence was 74.5% among men (178 of 239) and 70.6% among women (190 of 269). The highest antibiotic use was observed among children aged <1 year (98 of 108, 90.7%). Of the patients on antibiotics, 63% were treated with >1 antibiotic. In addition, 384 indications for antibiotic prescription were reported. Of the indications for antibiotics therapy, 49.7% (191 of 384) were for treatment, and 49% (188 of 384) were for prophylaxis. Of the treatments, 92% were empiric with 6% reported as targeted. Only 13% (50 of 370) of the patient records indicated that samples were taken for microbiological identification. Of those, 9 had results for culture, and 1 had results for drug susceptibility. The most commonly reported antibiotic was ceftriaxone (n = 110, 23%) followed by ampicillin (n = 153, 21.4%) and metronidazole (n = 135, 20%). Conclusions: This study shows high use of antibiotics among hospitalized patients in Haitian hospitals, especially in children aged <1 year. Almost all the antibiotics were prescribed as either empiric or prophylaxis therapy, with very few microbiology samples collected. These results suggest limited laboratory corroboration across hospitals to inform antibiotic use. Implementation of antimicrobial stewardship interventions is recommended to optimize antibiotic therapy and to mitigate antimicrobial resistance in hospital care settings, but adaptation of the methodology should be done in settings with limited laboratory capacity. Funding: None Disclosures: None